Members perceptions of financial services co-operatives :a case study of Motswedi, Lothlakane, Disaneng, Kraaipan and Lehurutshe - Mahlangu, Jenetha (University of Limpopo, 2015)
Financial Services cooperatives are member based financial institutions formed, owned and controlled by members to provide financial services to their members. The concept of cooperative banking is new in South Africa and it is promoted to address financial services needs of the rural poor who would otherwise have no means of accessing financial services and use from formal banks. The study was undertaken to determine members perceptions towards financial services co-operatives in Lehurutshe, Lothlakane, Motswedi, Kraaipan and Disaneng FSC’s in the Ngaka Modiri Molemo District of North West Province. Population included 236 participants who were selected using non-probability purposive and convenience sampling method. Different data collection methods, namely, Focus group discussion, Product attribute ranking, Likert-scale and questionnaires were used. Data was analysed using Statistical Package for the Social Sciences (SPSS) computer program and presented in descriptive statistics percentages and tables. The study revealed that FSC’s members were satisfied with services and products that were offered in the cooperatives; however issues of governance, fiduciary, regulatory and member participation require immediate attention. Recommendations to strengthen the regulatory framework for FSCs and FSCs’ institutional capacity were made.
Thesis (MSc. (Agricultural Extension)) -- University of Limpopo, 2015.
Keywords: Financial services cooperations; Cooperate banking; Financial Service Industry -- South Africa -- Limpopo Province